2022
DOI: 10.1002/ecs2.4068
|View full text |Cite
|
Sign up to set email alerts
|

Context dependence in a tropical forest: Repeated disturbance reduces soil nitrate response but increases phosphate

Abstract: Hurricanes and other extreme events are increasing in many regions, yet their long‐term impacts on ecosystem function are uncertain. In forested ecosystems, soil solution chemistry provides an important tool to assess the impacts of disturbance on nutrient cycling and dissolved organic carbon dynamics. Here, we address the dependence of soil solution chemistry on disturbance regime using a novel combination of both experimental and observational results collected over a period of 16 years in montane tropical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…We found N and P fluxes from green litter to soil were highest in bags with large mesh size in the trim + detritus treatment. Correspondingly, McDowell (in press) found in lysimeters located nearest our litterbags that nitrate accumulated more in groundwater in the trim + detritus than in the control treatment. The occurrence of a significant drought during this study could have uncoupled nutrient mineralization and root uptake, as observed previously following Hurricane Hugo (Lodge et al, 1994; McDowell et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
“…We found N and P fluxes from green litter to soil were highest in bags with large mesh size in the trim + detritus treatment. Correspondingly, McDowell (in press) found in lysimeters located nearest our litterbags that nitrate accumulated more in groundwater in the trim + detritus than in the control treatment. The occurrence of a significant drought during this study could have uncoupled nutrient mineralization and root uptake, as observed previously following Hurricane Hugo (Lodge et al, 1994; McDowell et al, 1996).…”
Section: Discussionmentioning
confidence: 53%
“…Lysimeters are used to collect soil solutions for analysis and can offer a path for investigating soil solution properties in their natural state. The study of soil solution hydrochemistry through lysimeters helps in understanding nutrient mobility and dynamics (e.g., Carey 2003 ; Johnson et al 2018 ; Petrash et al 2019 ; Makowski et al 2020 ; McDowell and Potter 2022 ), and can be used for evaluating the prevalence of toxicants in soils (e.g., Shaheen et al 2014 ; Worrall et al 1999 ). Many previous studies used lysimeters for developing the understanding on pollution processes, composition, and fluxes of vadose waters (Goss et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complexity in integrating and interpreting the multiple factors that weigh on measurable chemical properties of soil solutions-at any temporal scale-means that studies based on lysimeters placed and "equilibrated" under natural conditions are rather unusual. Nonetheless, the hydrochemistry of soil solutions can be useful to assess nutrient mobility and dynamics (e.g., Carey, 2003;Johnson et al, 2018;Petrash et al, 2019;Makowski et al, 2020;McDowell and Potter, 2022), and for evaluating the prevalence of toxicants in soils (e.g., Shaheen et al, 2014;Worrall et al, 1999). Many other previous studies used lysimeters for the developing understanding on pollution processes, composition, and uxes of vadose waters (see Goss et al, 2010 for a review).…”
Section: Introductionmentioning
confidence: 99%